OP82 An Evaluation of the Effect of the New School Food Policy on Children's Nutritional Intake and Socio-Economic Consequences in North East England. (17th September 2012) - Spence, S; Shen, J; Delve, J; White, M; Vale, L; Adamson, AJ
Abstract : Background: After 20 years with no regulation of school food and a plethora of evidence on the state of children's diets, new food and nutrient-based standards were re-introduced in 2006 to schools in England. As a major policy change receiving financial and legislative support from Government, our objectives were to evaluate the effect of this policy on children's nutritional intake, and its wider consequences including the added costs. Methods: A cross-sectional study was undertaken in primary (n=13) and middle (n=5) schools in North East England. Dietary, anthropometric and socio-economic data were collected from children aged 4–7y and 11–12y using identical quantitative methods pre, and post-implementation. In the 4–7y olds a four day food diary was completed using an observational method, the 11–12y olds completed 2x3 day food diaries followed by an interview. Economic analysis was conducted in the form of cost-consequence analysis, comparing the differences in costs with all of its possible consequences in a tabular format. Results: The effect of lunch type (school or packed) and year had a significant effect on total dietary intake in the 4–7y olds (n=1, 017). Children having school lunches post-implementation had a slightly higher mean daily intake of energy (93 kcals, p=0·004), but lower mean daily % energy from fat (3%, p<0·001) and saturated fat (1%, p<0·001). Mean daily intakes of micronutrients such as vitamin C, and iron were higher in children consuming school lunches. In contrast, there was limited evidence of the effect of lunch type post-implementation on the total diet in 11–12y olds (n=883). The exception was % energy from fat. In 1999–2000 children consuming a school lunch had a higher % energy from fat than those consuming a packed lunch, post-implementation this difference was no longer apparent. The cost per school meal following implementation of the school food policy is higher than pre-implementation, ranging from £29 to £55 per child per year depending on how differences in prices of food pre and post-implementation were adjusted for inflation. Wider social consequences, for example, a reduction in socio-economic inequality, educational benefits and change in health behaviour were also set against the increased cost. Conclusion: These findings demonstrate that the introduction of the school food policy has the potential to have a positive impact not only on food eaten at school but also on children's total diet. Economic analysis highlights the trade-offs between significant improvement of nutrient intakes of children and the increased cost.